Boiling Heat Transfer Enhancement by Self‐Assembled Graphene/Silver Hybrid Film for the Thermal Management of Concentrated Photovoltaics - Nurettin Sezer (14778217) (2020)
Graphene nanosheets have attracted appreciable interest in heat transfer augmentation due to the unique deposition characteristics. The porous morphology of the graphene deposited on the heating surface via self-assembly is reported to retard the transition boiling significantly. However, less attention has been paid to ameliorate the heat transfer coefficient (HTC) of graphene-dispersed solutions. Herein, silver ions are introduced into graphene nanofluids to ameliorate its HTC. During boiling, graphene nanosheets and silver nanoparticles simultaneously deposit on the heating surface to form a well-structured porous graphene/silver hybrid coating. The newly formed surface is characterized for surface morphology, wettability, and roughness. The new surface coating enhances the HTC by up to 109% and maintains the retarded critical heat flux of graphene-only nanofluids. The application of the enhanced boiling heat transfer for the thermal management of concentrated photovoltaics is studied. It is demonstrated that enhanced boiling allows for cogeneration of electricity and heat from concentrated photovoltaics at approximately fourfold increased production rate while maintaining efficient, safe, and reliable operation. Other Information Published in: Energy Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ente.202000532